Simultaneous Action of X- and O-Mode HF Pump Waves on the High-Latitude Upper (F-Region) Ionosphere at EISCAT - Nataly Blagoveshchenskaya; Tatiana Borisova; Alexey Kalishin; Ivan Egorov; Tim Yeoman; Ingemar Haggstrom (Universe, 2022)
We report experimental results from multi-instrument diagnostic tools related to phenomena in the high latitude ionosphere F-region, induced by the simultaneous action of powerful extraordinary (X-mode) and ordinary (O-mode) polarized HF radio waves at EISCAT (European Incoherent SCATter) during magnetically quiet background geophysical conditions. HF pump waves were injected towards the magnetic zenith at a frequency of 5.423 MHz, which was just below the critical frequency of the F2 layer when the excitation of X- and O-mode phenomena was possible. In the course of the experiment, the effective radiated power (ERP) of the X-mode wave was 130.5 MW, while the portion of the O-mode ERP was 29.9 MW (about 20% of the full ERP). It was found that simultaneous action of the X- and O-mode pump waves lead to the excitation of effects typical for both X- and O-mode HF pump waves. Namely, the excitation of small-scale field-aligned irregularities due to the thermal parametric (resonance) instability and a downshifted maximum (DM) component in the wideband stimulated electromagnetic emission (WSEE) spectra, typical for the O-mode HF pumping, was observed, together with multiple ion gyro-harmonic structures in the narrowband stimulated electromagnetic emission (NSEE) spectra. These latter results were recorded at a large (more than 1000 km) distance from the EISCAT/heating facility, typical only for an X-mode HF pumping. The results obtained are compared with “pure” O-mode heating and discussed in detail.